POLITICAL STUDIES OF REGIONAL AUTONOMY LAW IN TERMS OF THE IMPLEMENTATION OF THE POLITICAL PROMISES OF THE LEADER ELECTED IN RIAU PROVINCE - Afrinaldy Rustam; Sabarno Dwirianto (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The promise of polithic became a very important indicator for influencing voters. This study seeks to describe and analyze the political policies of the implementation and performance of the Governor of Riau, Syamsuar, after becoming the regional head of Riau Province. The purpose of this study was to analyze the political relevance of Syamsuar to political promises in Riau Province during his reign. This type of research is normative legal research. The data collection method used in this study is by conducting a literature study related to the object of this study. Data analysis in this study was carried out systematically based on research problems that were described qualitatively. The main theories used in this study are Public Policy and Power. The results of this study show that the political promises of Syamsuar have been implemented as a whole. However, there are some political promises that have not been realized according to people's expectations, especially in the field of infrastructure because they are developing slowly. This is due to the lack of development budgets and the problem of inefficiency in bureaucratic performance.